ZAMAN RADIKAL: DINAMIKA GERAKAN SOSIAL DI INDONESIA PADA MASA KOLONIALISME 1912-1926 - Shah Jahan, Muhammad Tristan (Universitas Negeri Yogyakarta, 2024)
ABSTRACTIn the historical track, social movements in Indonesia were characterized by the influence of political ideology and the role of intellectuals who initiated the action. The purpose of this scientific article is to examine the dynamics of social movements in Indonesia that occurred during the national movement, when Indonesia entered a radical and non-cooperative era against colonialism. Through the historical method approach and the library research method, a new view can be found about the social movement pattern consisting of labor strikes and armed rebellions as well as the role of intellectual figures and the influence of socialism that mobilized anti-colonial mass elements.